Fundamental aspects of the current setting of the disciplinary power of the Spanish public administration over its personnel - Marina Jalvo, Belén (2020)
The basic regulation of the guiding principles of the exercise of the Spanish Public Administration’s disciplinary power over its personnel, and the principles of the procedure for exercising this power, is stipulated in Royal Legislative Decree 5/2015, of 30 October, which approves the Revised Text of the Law of the Basic Public Employees Statute (BPES). These provisions are completed with the regulations that must be issued by the Spanish Government and the Autonomous Communities. The Spanish Government has not yet passed legislation applicable to its own personnel. The BPES formulated the guiding principles of disciplinary authority under very similar terms to the general principles that govern the exercise of the administrative power to impose penalties.The jurisprudence concerning contentious-administrative matters interprets and completes the regulatory framework of disciplinary law, considered to fall within Administrative Law, while at the same time contributing to outlining the characteristics of the principles of the administrative power to impose penalties as it applies to the disciplinary field.